Crystal structures of phosphine-supported (η5-cyclopentadienyl)molybdenum(II) propionyl complexes - Matthew T. Whited; Margaret A. Ball; Alison Block; Benjamin A. Brewster; LouLou Ferrer; Helen J. Jin-Lee; Colby J. King; Jamie D. North; Inger L. Shelton; David G. Wilson (Acta Crystallographica Section E: Crystallographic Communications, 2021)
Three cyclopentadienylmolybdenum(II) propionyl complexes featuring triarylphosphine ligands with different para substituents, namely, dicarbonyl(η5-cyclopentadienyl)propionyl(triphenylphosphane-κP)molybdenum(II), [Mo(C5H5)(C3H5O)(C18H15P)(CO)2], (1), dicarbonyl(η5-cyclopentadienyl)propionyl[tris(4-fluorophenyl)phosphane-κP]molybdenum(II), [Mo(C5H5)(C3H5O)(C18H12F3P)(CO)2], (2), and dicarbonyl(η5-cyclopentadienyl)propionyl[tris(4-methoxyphenyl)phosphane-κP]molybdenum(II) dichloromethane solvate, [Mo(C5H5)(C3H5O)(C21H21O3P)(CO)2]·CH2Cl2, (3), have been prepared from the corresponding ethyl complexes via phosphine-induced migratory insertion. These complexes exhibit four-legged piano-stool geometries with molecular structures quite similar to each other and to related acetyl complexes. The extended structures of the three complexes differ somewhat, with the para substituent of the triarylphosphine of (2) (fluoro) or (3) (methoxy) engaging in non-classical C—H...F or C—H...O hydrogen-bonding interactions. The structure of (3) exhibits modest disorder in the position of one Cl atom of the dichloromethane solvent, which was modeled with two sites showing approximately equivalent occupancies [0.532 (15) and 0.478 (15)].